The correlation between a Th1/Th2 cytokines imbalance and vitamin D level in patients with early chronic obstructive pulmonary disease (COPD), based on screening results - Tang, Wenhui; Rong, Yan; Zhang, Hongmei; Zhan, Zi’e; Yuan, Long; Ning, Yan; Lin, Wenji (Frontiers in Physiology, 2023)
Objective: This study explored the correlation between a Th1/Th2 cytokines imbalance and 25-hydroxy-vitamin D (vit D) level in early chronic obstructive pulmonary disease (COPD), provided experimental rationales for the role of vit D in the prevention and control of COPD, and elucidated the potential anti-inflammatory mechanism involved. Methods: This study was based on the results of the “Screening and Early Diagnosis of COPD” public health project conducted through Shenzhen Municipal Qianhai Shekou Free Trade Zone Hospital. Patients with early COPD were selected as study participants. A prospective, randomized, and controlled method was employed for assigning eligible participants into three groups, i.e., a COPD lung function (LF) I, COPD LF II, and a healthy group, respectively (n = 40 each). The serum content of tumor necrosis factor alpha (TNF-α), interferon-gamma (IFN-γ), interleukin 4 (IL-4), and IL-6 were measured by enzyme-linked immunosorbent assay, and the ratio of IFN-γ/IL-4 treated as a marker for Th1/Th2. The serum concentration of 25-hydroxyl-vit D (25[OH]D) was quantified by a chemiluminescence assay. Statistical processing was performed, and the correlations between changes in the above parameters with vit D level and LF parameters were examined. Results: There were differences in FEV1pred%, FEV1/FVC, IFN-γ, IL-4, IL-6 and IFN-γ/IL-4 between the healthy group, the COPD LF I group and the COPD LF II group (P<0.05). In early COPD, Th1/Th2 cytokines was positively correlated with forced expiratory volume/expected value (FEV1pred%) (r=0.485, P<0.001) and forced expiratory volume/forced vital capacity (FEV1/FVC) (r=0.273, P=0.018); Th1/Th2 cytokines levels positively correlated with vit D level (r=0.27, P=0.02), and 25(OH)D level positively correlated with FEV1pred% (r=0.695, P<0.001）. Conclusions: Vitamin D deficiency was ubiquitous in patients with early COPD. It was positively correlated with the FEV1pred% and FEV1/FVC LF parameters. Accordingly, this study provides experimental rationales for the role of vit D in the prevention and control of COPD and the potential anti-inflammatory mechanisms involved.